Are ACE inhibitors safe to use in patients with chronic kidney disease?. Issue 7 (July 2018) - Attia, Maximos; Sprentall, Kelcie; Dzafic, Alma
Abstract : EVIDENCE‐BASED ANSWER : Yes. In patients with chronic kidney disease (CKD), angiotensin‐converting enzyme (ACE) inhibitors do not increase mortality, cardiovascular events, or progression to end‐stage renal disease (ESRD) compared with either calcium channel blockers (CCBs) or placebo, while leading to a 49% reduction in doubling of creatinine and being relatively well tolerated (SOR: A, 2 meta‐analyses of RCTs).